The 'Musica instrumentalis deudsch' of Martin Agricola - Hettrick, William E. (Cambridge Cambridge University Press, 1994)
Martin Agricola (1486-1556) was an important early Lutheran musician and teacher from Saxony and his treatises were intended as textbooks in musical performance. Highly illustrated, they give practical instruction on a number of musical instruments, showing methods of fingering, tuning and notation. As such they are valuable sources of information about the study and performance of music in Germany in the early sixteenth century. The first Musica instrumentalis deudsch, written mostly in rhymed German verse and containing woodcut diagrams and depictions of musical instruments, appeared in 1529. It was modelled on the Musica getutscht (Basel 1511) of Sebastian Virdung, copying many of the woodcuts found in the earlier work and redefining its classification of musical instruments. A revised and almost completely rewritten edition of Agricola's treatise was published in 1545.This is the first translated, modern edition of this famous treatise on musical instrumentsIt is very important for all those interested in performance practice, playing on early instruments and 'authenticity'This treatise is modelled closely on Virdung's Musica getutscht
Keywords: 16th Century (1501-1600); Organology